“The very interesting finding suggests that…”: A cognitive frame-based analysis of interest markers by authors’ geo-academic location in applied linguistics research articles - Wang, Qian (Frontiers in Psychology, 2022)
Linguistic expressions of interest instantiated by interesting, intriguing, and fascinating that signal the authorial stance are not uncommon in applied linguistics research articles. Nevertheless, they have received little scholarly attention. This paper, taking a cognitive semantic approach, reports on a study that sought to examine how linguistically expressed interest in applied linguistics research articles is leveraged by researchers’ geo-academic location (the Core vs. the Periphery). Drawing on a semantic frame generated for interest markers in academic writing, this study focused on the incidence of the various elements of the Interest frame in the discipline of applied linguistics based on a mixed-methods approach. The corpus-based quantitative analyses found that academic writers’ geo-academic location was a robust predictor of authors’ overall use of interest markers and some frame elements associated with the Interest frame. Triangulation with the interview data obtained from disciplinary specialists revealed that the observed differences could be attributable to the hierarchical academia featuring periphery-based scholars’ unequal access to the knowledge production market and under-representation.